2021
DOI: 10.1016/j.intimp.2021.107871
|View full text |Cite
|
Sign up to set email alerts
|

Mometasone furoate nasal spray in the treatment of patients with COVID-19 olfactory dysfunction: A randomized, double blind clinical trial

Abstract: The aim of this study was to evaluate the usage of mometasone furoate nasal spray in the recovery of patients with severe microsmia or anosmia induced by COVID-19. This was a prospective clinical trial on non-hospitalized adult patients with COVID-19 (> 18 years) who had severe microsmia or anosmia within two weeks. The subjects were randomly assigned to the mometasone furoate group (100 mcg twice daily) or sodium chloride group (0.9%); both groups also received olfactory training for 4 weeks. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 22 publications
3
75
0
2
Order By: Relevance
“…Psychophysical tests such as the University of Pennsylvania Smell Identification Test provide more reliable assessments of olfactory symptoms than self‐report measures, and inconsistency in the methods used for olfactory assessment can lead to heterogeneity in the results. 7 Interestingly, two of the studies included in our meta‐analysis showed that topical steroids were either not significantly more effective or less effective than the control, although two others showed that steroids were an effective treatment. The former two studies had younger patient cohorts.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Psychophysical tests such as the University of Pennsylvania Smell Identification Test provide more reliable assessments of olfactory symptoms than self‐report measures, and inconsistency in the methods used for olfactory assessment can lead to heterogeneity in the results. 7 Interestingly, two of the studies included in our meta‐analysis showed that topical steroids were either not significantly more effective or less effective than the control, although two others showed that steroids were an effective treatment. The former two studies had younger patient cohorts.…”
Section: Discussionmentioning
confidence: 87%
“… 4 , 12 The outcomes of interest were the post‐treatment olfactory score (2 and 4 weeks after the initiation of treatment were analysed referring to the common analysis time point of the included papers) and percentage of patients with a full recovery. 7 , 10 , 11 , 13 , 14 These outcomes were compared between the treatment (topical steroid) and control groups; the latter were administered either saline or nothing. When the original data were expressed as continuous variables, the meta‐analysis was performed using the standardised mean difference (SMD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current Position Paper on Olfactory Dysfunction [ 14 ], olfactory training is the recommended therapy for post-infectious OD. Based on multiple studies that reveal beneficial features of olfactory training [ 39 42 ], daily practicing with four odourants has become standard recommendation of COVID-19 related OD. Despite smell training, different centers studied the effect of cortisone—intranasal as well as oral—on the outcome regarding OD.…”
Section: Discussionmentioning
confidence: 99%
“…In a case–control study with 50 patients in each group (olfactory training solely vs. olfactory training and intranasal cortisone) the self-assessment of smell did not differ between the groups [ 41 ]. Furthermore, Kasiri et al revealed no significant difference concerning SAS and psychophysical tests (the Iran Smell Identification Test) between intervention (intranasal cortisone and olfactory training) and control (solely olfactory training) group [ 42 ]. Whereas, another case–control study showed a significant improvement of psychophysically evaluated smell function after olfactory training and 10 days of oral cortisone.…”
Section: Discussionmentioning
confidence: 99%